Síndrome coronario agudo sin supradesnivel ST. Diagnóstico y tratamiento inicial - Ugalde P., Héctor (Revista Hospital Clínico Universidad de Chile, 2018)
Coronary heart disease can manifest as stable or unstable forms, being these variationsdifferentiated mainly by the underlying pathophysiological cause, their clinical presentationand the risk associated to each of these clinical presentations. In the unstable form, nowadaysknown as acute coronary syndrome, recommendations over its characterization and particularlyits management are periodically updated in published international guidelines about this topic.Their epidemiological relevance makes important that these aspects should be known byanyone that sees patients in their practices, motivating this review in which we will summarizeaspects of the clinical presentation, initial studies and management of the acute coronarysyndrome without ST segment elevation emphasizing novelties from the last few years.